Biocompatibility and paclitaxel/cisplatin dual-loading of nanotubes prepared from poly(ethylene glycol)-polylactide-poly(ethylene glycol) triblock copolymers for combination cancer therapy - Shen, Xin (Saudi Pharm J, 2019)
Nanotubes were prepared by self-assembly of the copolymer using co-solvent evaporation method. The biocompatibility of the nanotubes was assessed in comparison with spherical micelles and filomicelles prepared from poly(ethylene glycol)-poly(L-lactide-co-glycolide) (PEG-PLGA) and poly(ethylene glycol)-poly(L-lactide) (PEG-PLA), respectively. Several aspects of biocompatibility of the aggregates were considered, including agar diffusion and MTT assay, release of cytokines, hemolysis, protein adsorption, dynamic clotting in vitro, and Zebrafish embryonic compatibility in vivo. The nanotubes present good cell compatibility and blood compatibility in vitro, and almost no toxicity towards Zebrafish embryos development in vivo. Furthermore, dual-loading of hydrophilic cisplatin and hydrophobic paclitaxel was achieved in the nanotubes with high loading content and loading efficiency. The release of both drugs was slower from dual-loaded nanotubes than from single-loaded ones, but the total amount of released drugs in higher for dual-loaded nanotubes than from single-loaded ones. Cellular uptake and inhibition tests showed that the nanotubes were successfully taken up by tumor cells and effectively inhibited cell growth. It is thus concluded that PEG-PLA-PEG nanotubes with outstanding biocompatibility could be promising for co-delivery of hydrophilic and hydrophobic agents in combination cancer therapy.